Cover Feature: Electrochemical Hydrodimerization of Furfural in Organic Media as an Efficient Route to Jet Fuel Precursor (ChemElectroChem 2/2023). Issue 2 (21st December 2022) - Temnikova, Maria; Medvedev, Jury; Medvedeva, Xenia; Delva, Nyhenflore H.; Khairullina, Evgeniia; Krivoshapkina, Elena; Klinkova, Anna
Abstract : The Cover Feature illustrates that biomass‐derived furfural can be electrochemically converted to a jet fuel precursor. More information can be found in the Research Article by M. Temnikova et al .